Evaluation Of A Web-Based Teledentistry Application As An Assessment And Follow-Up For Oral And Maxillofacial Surgery Patients Using The Sus (System Usability Scale) Method - Dhiya Afiyah Iskandar; Moh Husnun Niam (Jurnal Medali, 2026)
Background: Teledentistry is an innovation in web-based dental health services that enables dentists and patients to communicate remotely without direct contact. This application plays an essential role in the assessment and follow-up of oral and maxillofacial surgery patients. This study aimed to evaluate the usability level of a web-based teledentistry application using the System Usability Scale (SUS) method.Method: This study was a descriptive observational research with a non-experimental case study approach. Data were obtained using a SUS questionnaire consisting of 10 Likert-scale questions assessing three main aspects: effectiveness, efficiency, and user satisfaction toward the RamahCLP web application.Result: The results showed that the web-based teledentistry application achieved a good usability score, categorized as “acceptable,” indicating that users could easily understand and operate the application for assessment and follow-up needs.Conclusion: It can be concluded that the RamahCLP web-based application has good usability and has the potential to effectively support teledentistry services.